Трипільське поселення Василівка на Середньому Дністрі - Шумова, В.О. (Археологія, 1994)
Аналізуються матеріали Трипільського поселення періоду ВІ — Кукутені А₃₋₄ Трипільської культури. Розглядаються особливості домобудування, керамічний комплекс. В статье систематизируются материалы трипольского поселения у с. Васильевка на Среднем Днестре (Сокирянский р-н Черновицкой обл,), датируемого Периодом В1 Триполья — Кукутень А₃₋₄. Рассматриваются детали топографии и планировки поселения, некоторые технические приемы домостроительства. Основное внимание уделяется анализу керамического комплекса, своеобразие которого состоит в сохранении ряда черт, присущих предшествующему этапу и, прежде всего, отразившихся в технологических и стилистических признаках. Прослеживаются некоторые вопросы развития памятников финала этапа В1, причем наблюдается взаимодействие традиционных местных и инновационных элементов. Отсутствие же прямых аналогий и равноценно исследованных памятников этапа В1 определило круг сопоставлений на широком фоне памятников данного этапа территории Украины, Молдовы, Румынии. Публикуемые материалы значительно дополняют фактологическую базу развитого Триполья. In the paper the materials of the Tripolian settlement near Vasilievka village at Middle Dniester (Sokimoje district Tchemovitzy region) which dates to the period R1 of Tripolie— Kukuteni A₃₋₄ are systematizated. The details of the topography and lay-out of the settlement, the certain technical methods of building are considered. The main attention is paied to the analysis of corpus of pottery which originality consists of a preservation of a number of features inherent in the previous stage and reflected first of all by technological and stylistic indications. Some problems of the development of memorials of the final of stage B2 are considered. It is observed the interaction of the traditional native elements and the innovational ones. Jast the absence of the direct analogies and equivalently researched memorials of the stage B1 has marked the range of the comparision against the broad background of memorials dated to this stage from Ukraine, Moldova, Romania. The publicated materials considerably enrich the factological base of the welldeveloped Tripolie.